What types of dissemination of information occurred between researchers, providers and clinical staff while implementing an asthma shared decision-making intervention: a directed content analysis. Issue 3 (8th March 2020) - Ludden, Thomas; Shade, Lindsay; Welch, Madelyn; Halladay, Jacqueline; Donahue, Katrina E; Coyne-Beasley, Tamera; Bray, Paul; Tapp, Hazel
Abstract : Objective: To qualitatively analyse different types of dissemination of information during monthly group calls between researchers, providers and clinical staff used to establish best practices for implementing an asthma shared decision-making (SDM) intervention. Evaluating dissemination of information can provide a better understanding of how best practices are shared, informing implementation approaches to improve the uptake of new evidence and overcome barriers. Setting: 10 primary care practices in North Carolina. Participants: Providers and clinical staff participated in monthly group phone calls with researchers to share best practices during implementation of a SDM intervention for asthma patients. Design: The research team transcribed and coded statements using content analysis into three different knowledge types: Knowledge Position, Knowledge Form and Knowledge Object. Knowledge Objects were further classified using directed content analysis where the research team interpreted the content objects through a classification process of identifying themes or patterns to describe three different types of dissemination of information: (A) Confirmation of Existing Knowledge, (B) Generation of New Knowledge and (C) Spreading of New Knowledge. Results: Across the 8 transcripts, 4 Knowledge Positions, 7 Knowledge Forms and 18 types of Knowledge Objects were identified. From the Knowledge Objects, Confirmation of Existing Knowledge occurred during the training of participating practices. The review also identified Generation of New Knowledge by providers and clinical staff raised in these calls. This Generation of New Knowledge was later documented being used by other practices with the identification of Spreading of New Knowledge. Conclusion: The research team described the types of dissemination of information that occurred between researchers, providers and clinical staff during implementation of an asthma SDM intervention. Both Confirmation of Existing Knowledge and Generation of New Knowledge in response to barriers occurred. These exploratory dissemination of information results provide additional mechanisms for evaluating implementation science. Trial registration number: NCT02047929 ; Post-results